KERAJAAN-KERAJAAN ISLAM ZAMAN PENJAJAHAN BELANDA - Muhammad Basri; Indah Afrilia Hasibuan, Elfina Yanti Siregar, Mutiara Alya Hasyim, Fitrah Isna Muhabbah (Jurnal Salome : Multidisipliner Keilmuan, 2024)
The Islamic kingdoms in Indonesia experienced many changes during the Dutch colonial period. At the beginning of colonialism, the Dutch implemented policies that supported the success of their expansion in Indonesian territory, including the expansion of government areas. The Islamic kingdoms in the archipelago can be said to be maritime kingdoms, because their centers of power were in port cities. Since the beginning of establishing Dutch rule in the Netherlands New Guinea (Papua), the Netherlands implemented policies that supported the success of its expansion in that region. One of the policies implemented by the Netherlands in the region was the expansion of government areas.